General chemistry - Ebbing, Darrell D.; wrighton, Mark S. ([S.l.] : Houghton Mifflin College Div, 1996)
Known for its carefully developed, thoroughly integrated approach to problem solving, this market-leading text emphasizes the conceptual understanding and visualization skills essential for first-year chemistry and science majors. The new technology program reinforces the approach of the text and provides a complete solution for teaching and learning. The Eighth Edition retains the hallmark pedagogical features of the text and builds upon the conceptual focus and art program. Students also benefit from online homework in the technology program, which features an extensive database of questions drawn from the text.In order to reinforce major chemical concepts, the authors present a proven six-part approach to problem solving that includes "Example, Problem Strategy, Solution, Answer Check, Exercise," and corresponding "End-of-Chapter Problems," many of which are presented in matched pairs.The Media Integration Guide for Instructors includes several user-friendly supplements designed to make class preparation, presentation, and course management more efficient and effective: HM ClassPrep/HM Testing CD-ROM; HM ClassPresent CD-ROM with animations; instructor web site access; and information about Eduspace (powered by Blackboard). Eduspace is Houghton Mifflin's online learning tool. Powered by Blackboard, Eduspace is a customizable, powerful and interactive platform that provides instructors with text-specific online courses and content. This Ebbing et al. "General Chemistry" course features test bank material for exams, algorithmic in chapter and dynamically generated end-of-chapter homework problems from question pools and access to ACE quiz content for independent practice. For theinstructor, we also provide presentation slides, photos, illustrations, interactive tables and video clips. The Media Guide for Students provides information on and access to multimedia tools that help students visualize chemical concepts and practice problem-solving strategies: SMARTHINKING live online tutoring, student web site with animations, and Student CD-ROM. The guide also includes information about Eduspace (powered by Blackboard).
Keywords: chemistry,general chemistry